Potensi Infusa Daun Tradescantia spathaceae Sebagai Tabir Surya pada Sediaan Gel Menggunakan Metode Spektrofotometri UV-Vis - Rani Rubiyanti; Nur Aji (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
The boat lily (Tradescantia spathaceae) leaves have purple pigments produced from anthocyanins. This compound is thought to have sunscreen activity. The purpose of this study was to test the potential of sunscreen for both infusion and gel preparations of boat lily leaves in vitro using a spectrophotometric UV-Vis and determine its stability. The gel formula with a concentration of 12.5%; 25% and 50%. The parameters observed in this study were organoleptic, homogeneity, pH, dispersion test, viscosity, the value of Sun Protection Factor (SPF), and storage time test. The greater concentration of infusions, the lower the viscosity and inversely proportional to the dispersion value. The preparation has a good pH and follows the skin’s pH, which is in the range of 5.87-7.00. The boat lily infusion has SPF values: 3.64; 6.83, and 12.73. In comparison the boat lily gel has SPF in succession, namely: 7.48; 9.55, and 14.06. Based on the research, it can be concluded that the infusion of the boat lily can be made in a gel dosage form. Both infusion and infusion gel preparations of pineapple shellfish at a concentration of 12.5% to 50% have low protective power and boat lily infusion gel is unstable during storage.